Germanizmi v frazemih Slovarja slovenskega knjižnega jezika od M do P - Stramljič Breznik, Irena (Slavia Centralis, 2020)
Germanisms in Idioms Included in the Dictionary od Slovene Literary Language (SSKJ) from M to P This article examines the Germanisms included in the Dictionary of Slovene Literary Language (SSKJ) from M to P which are also idiom ingredients. With the support of the reference corpus Fidaplus, presence in contemporary use is stated, and, consequently, answers to the questions how many and what kind of idioms would be reasonable to take into account in the new issue of the Dictionary of Slovene are suggested.